On the Valuations of the Near Polygon Hn - De Bruyn, Bart (Annals of combinatorics, 2018)
We characterize the valuations of the near polygon H n that are induced by classical valuations of the dual polar space D W ( 2 n - 1 , 2 ) into which it is isometrically embeddable. An application to near 2 n -gons that contain H n as a full subgeometry is given.